Total Syntheses of Lyconadins: Finding Efficiency and Diversity - Yang, Yang; Dai, Mingji (Synlett, 2014)
Lyconadins A–C are important members of the Lycopodium alkaloid family with challenging structural features and interesting biological profiles. Herein, various synthetic strategies and methods for their preparation are summarized with the focus on constructive bond formation and our efficient and divergent synthesis based on a functional group pairing (FGP) strategy.
Keywords: alkaloid; total synthesis; natural product; cyclization; neurodegeneration